Soy protein hydrolysate grafted cellulose nanofibrils with bioactive signals for bone repair and regeneration. (1st February 2020) - Salama, Ahmed; Abou-Zeid, Ragab E.; Cruz-Maya, Iriczalli; Guarino, Vincenzo
Highlights: Cellulose nanofibrils were successfully grafted with soy protein hydrolysate. Calcium Phosphates via SBF treatment improve the bioactivity of cellulose nanofibrils. In vitro studies confirmed the biocompatibility of grafted materials. Mineralized SPH grafted cellulose nanofibrils are promising for the repair and/or the regeneration of hard tissues. Abstract: TEMPO oxidized cellulose nanofibers (T-CNF) were prepared from cellulose pulp which is extracted from bagasse. Soy protein hydrolysate (SPH) was grafted on T-CNF via amidation of carboxylic groups. Biomineralization was, then, assessed via calcium phosphates (CaP) precipitation in twice-simulated body fluid until formation of a new bioactive material. Protein was efficiently grafted without alteration of morphology and nanofibrils packing as reported by Fourier Transform infrared analysis /X Ray Diffraction /Scanning and Transmission Electron Microscopy / Atomic Force Microscopy. Highly crystalline calcium phosphate deposits - ca. 22.1% - were detected, with a Ca/P ratio equal to 1.63, in agreement with native bone apatite composition. In vitro response of human Mesenchymal Stem Cells confirmed the biocompatibility. No significant differences in terms of cell adhesion were recognized while a significant increase in cell proliferation was detected until 7 days. The presence of calcium phosphates tends to cover the nanofibrillar pattern, inducing the inhibition of cell proliferation and promoting the ex-novo precipitation of mineral phases. All the results suggest a promising use of these biomaterials in the repair and/or the regeneration of hard tissues such as bone.